Diffusion and Adoption of new rice varieties for Africa (Nerica) in the Gambia. - Dibba, L.; Diagne, A.; Fialor, S.C.; Nimoh, F. (2012)
Rice (Oryza sativa) is one of the most important cereal crops cultivated in sub-Saharan Africa (SSA). It is rankedas the fourth most important crop in terms of production after sorghum (Sorghum bicolor), maize (Zea mays)and millet (Eleusine coracana). The objective of this study was to establish adoption rates, and their determinants,of the New Rice Varieties for Africa (NERICA) in the Gambia. We used data from a stratified sample of 600 ricefarmers and applied the Average Treatment Estimation (ATE) framework to establish rate of adoption andassociated factors. The results revealed that NERICA adoption rate was barely 40% falling far below theexpected 83%. The shortfall was due to the incomplete stakeholder exposure to NERICA in the period before2006. The introduction of NERICA to villages was found to be a significant determinant of both exposure andadoption of NERICA varieties.